Development, characterization and in vivo antibacterial and antioxcidant study of a coconut milk-based kefir beverage - Mahmood Taleb Abadl, Muna (2023)
Kefir, a fermented beverage traditionally produced from cow's milk using kefir grains, faces challenges due to the global shift away from dairy products driven by concerns such as lactose intolerance, milk allergies, and environmental impacts. To address this, the present study was undertaken to develop a plant-based alternative – coconut milk kefir. This research aims to explore the effect of fat content on the physicochemical, nutritional, and biochemical characteristics of Reduced Fat Coconut Milk Kefir (RFCMK) and High Fat Coconut Milk Kefir (HFCMK), optimize the pH, antibacterial, and antioxidant properties of coconut milk kefir, evaluate its biochemical, metabolomic, sensory attributes, and shelf life, and assess its in vivo antibacterial and antioxidant effects. In the investigation of fat content's influence on beverage properties, RFCMK exhibited higher lactic acid bacteria (LAB) growth and superior antibacterial activity against Bacillus subtilis (94.62±2.46%), Staphylococcus aureus (96.82±0.8%), Escherichia coli (100±1.63%), and Salmonella Typhimurium (98.67±1.37%) through antibacterial inhibitory tests. Furthermore, RFCMK demonstrated significantly elevated levels of DPPH, ABTS, and FRAP compared to HFCMK. Remarkably, through Response Surface Methodology (RSM), an optimal formulation was achieved solely by adjusting fermentation parameters, resulting in high antimicrobial activity (93.1 – 100%) against various pathogens and robust antioxidant properties (DPPH: 72.6%, ABTS: 47.06%, FRAP: 437.045 μM TE/100 mL). Metabolomic analysis using 1H–NMR revealed significant changes in metabolites like lactic acid, GABA, Biotin, Riboflavin, Butyrate, and Caprylate during fermentation, known to enhance antioxidant status and reduce lipid peroxidation. LC-MS/MS (Q-TOF) also identified 11 bioactive peptides with antibacterial properties. Consumer acceptability comparisons between cow's milk and coconut milk kefir showed no significant difference between the two products based on a 9-point hedonic scale. During a 30-day storage period at 4°C, syneresis significantly increased after day 15, accompanied by a gradual rise in acidity, reaching pH 3.5 by day 17. The microbial count of LAB and yeast dropped below the Codex Alimentarius Commission recommended values of 7.00 and 4.00 Log CFU/mL after days 17 and 14, respectively. In vivo assessment of the optimized coconut milk kefir in Wistar rats revealed increased LAB levels in the cecum, reduced Alkaline Phosphatase (ALP) and Aspartate Transferase (AST) levels, elevated High-Density Lipoprotein (HDL) levels in the blood, and heightened Total Superoxide Dismutase (T-SOD) levels in the liver. In conclusion, this study highlights the potential of coconut milk kefir as a healthy, plant- based alternative to traditional dairy kefir. Its diverse benefits include improved antibacterial and antioxidant properties, appealing sensory characteristics, and positive in vivo health effects, offering a promising option for those seeking dairy-free fermented beverages.